Literature's elsewheres on the necessity of radical literary practices - Gilbert, Annette 1975- (The MIT Press, 2022)
"Investigating experimental and avant-garde works of art as literature, Gilbert probes what art can't see about the literary and what literature has overlooked in the arts"--Provided by publisher.